Effects of Social Norms and Social Networks on Non-Smoking Behavior among Junior High School Adolescents in Boyolali, Central Java, Indonesia - Budi Santoso; Argyo Demartoto; Revi Gama Hatta Novika; Haryani Saptaningtyas; Yulia Lanti Retno Dewi (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Smoking behavior among adolescents remains a public health problem that may lead to long-term health consequences. Junior high school students are a vulnerable population at risk of engaging in smoking behavior due to social environmental influences, particularly from peers and family members. Social norms and social networks play an important role in shaping adolescents’ ability to maintain non-smoking behavior. This study aimed to analyze the effects of social norms and social networks on non-smoking behavior among junior high school students in Boyolali Regency. Subjects and Method: This study employed a quantitative research method with a cross-sectional design. The population consisted of 33,700 junior high school adolescents in Boyolali Regency. A total of 240 respondents were included in this study, and the data were collected using a stratified random sampling technique. The samples were obtained from eight junior high schools in Boyolali Regency, comprising four public junior high schools and four private junior high schools. Results: Based on Table 4, social norms had a significant effect on non-smoking behavior. Respondents with high social norms were 7.34 times more likely to engage in non-smoking behavior than those with low social norms (AOR = 7.34; 95% CI = 3.48 to 15.49; p = 0.001). Social networks also had a significant effect on non-smoking behavior. Respondents with high social networks were 7.78 times more likely to engage in non-smoking behavior than those with low social networks (AOR= 7.78; 95% CI= 3.68 to 16.43; p= 0.001). Gender was significantly associated with non-smoking behavior. Female respondents were 2.52 times more likely to engage in non-smoking behavior than male respondents (AOR = 2.52; 95% CI = 1.22 to 5.21; p = 0.012). Conclusion: Social norms and social networks significantly influenced non-smoking behavior among junior high school adolescents in Boyolali Regency.